The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5114/ceji.2012.32731
|View full text |Cite
|
Sign up to set email alerts
|

Role of UVA1 phototherapy in treatment of scleroderma and scleroderma-like disorders”

Abstract: Treatment of scleroderma and scleroderma-like diseases poses a serious challenge to contemporary dermatology due to the complexity of its pathogenesis, low incidence of the diseases and their heterogenous clinical expression. the manifestation of this autoimmune disease includes an increased production and deposition of collagen fibres types I and III in the skin and connective tissue as well as vascular alterations. Ultraviolet A1 (UVA1) phototherapy affects various stages of a morbid process in scleroderma: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…UVA1‐induced effects occur through oxygen‐dependent mechanisms in which endogenous absorption of energy by lipids and proteins occurs and then the resulting oxidized lipids/proteins are responsible for the UVA effect . The singlet oxygen ( 1 O 2 ) is generated after UVA1 irradiation of T lymphocytes and contributes its efficacy in treating inflammatory disease . In addition, ultraviolet A radiation (UVAR) excites the generated intracellular molecule 1 O 2 , then activates the apoptotic p38 and JNK, thus inducing the MAPK cascades .…”
Section: Uv Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…UVA1‐induced effects occur through oxygen‐dependent mechanisms in which endogenous absorption of energy by lipids and proteins occurs and then the resulting oxidized lipids/proteins are responsible for the UVA effect . The singlet oxygen ( 1 O 2 ) is generated after UVA1 irradiation of T lymphocytes and contributes its efficacy in treating inflammatory disease . In addition, ultraviolet A radiation (UVAR) excites the generated intracellular molecule 1 O 2 , then activates the apoptotic p38 and JNK, thus inducing the MAPK cascades .…”
Section: Uv Radiationmentioning
confidence: 99%
“…Several mechanisms are involved in UVA1 phototherapy such as apoptosis in various skin cell types (T or B lyphocytes, mast cells), modification of the effects of pro‐inflammatory cytokines, as well as lowering of the number of mast cells and Langerhans cells in the epidermis . It has recently been reported that UVA1 phototherapy may promote angiogenesis, the process of new blood vessel formation, in order to cure the skin diseases . During the phototherapy of vitiligo, psoriasis, and T‐cell lymphoma, the UV irradiation diminishes inflammation, reduces scaling, and consequently, promotes repigmentation at the exposed skin .…”
Section: Uv Radiationmentioning
confidence: 99%